Analisis Penerapan Praktik Ijarah dalam Jasa Pengolahan darah dalam Perspektif Hukum Ekonomi Syariah (Studi Kasus di PMI Kota Makassar) - Muh. Fahri Amin; M. Hasibuddin; Subaedah S (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the stages of blood donor processing at the Indonesian Red Cross (PMI) Makassar City Branch and to analyze the implementation of ijarah practices in blood processing services from the perspective of Islamic Economic Law. This research employs a field research approach using a qualitative descriptive method. Data were collected through interviews, observations, and documentation conducted at PMI Makassar City. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the blood donor processing at PMI Makassar City is carried out systematically, beginning with donor registration, health screening, blood collection, laboratory testing, blood component separation, storage, and finally the distribution of blood to patients in need. The fees charged to blood recipients do not represent the price of blood itself but rather the cost of blood processing services, including testing, processing, storage, and distribution. From the perspective of Islamic Economic Law, this practice can be categorized as an ijarah contract (ujrah), as it involves the provision of services in exchange for a specified compensation. The practice fulfills the essential pillars and conditions of ijarah, namely the contracting parties ('aqidain), the subject matter of the contract in the form of blood processing services (ma'qud 'alaih), clearly determined compensation (ujrah), and mutual consent (shighat).